Comparison of steam pasteurization and other methods for reduction of pathogens on surfaces of freshly slaughtered beef - Phebus, Randall K.; Nutsch, Abbey L.; Schafer, David E.; Wilson, R. Craig; Riemann, M. James; Leising, Jerome D.; Kastner, Curtis L.; Wolf, John R.; Prasai, Ram K. (My University, 2008)
The effectiveness of a recently invented "steam pasteurization" (S) process in reducing pathogenic bacterial populations on surfaces of freshly slaughtered beef was determined and compared with that of other standard commercial methods including knife trimming (T), water washing (35°C; W), hot water/steam vacuum spot cleaning (V), and spraying with 2% vol/vol lactic acid (54°C, pH 2.25; L). These decontamination treatments were tested individually and in combinations. Cutaneus trunci muscles from freshly slaughtered steers were inoculated with feces containing Listeria monocytogenes Scott A, Escherichia coli O157:H7, and Salmonella typhimurium over a predesignated meat surface area, resulting in initial populations of ca. 5 log CFU/cm2 of each pathogen. Tissue samples were excised from each portion before and after decontamination treatments, and mean population reductions were determined. Treatment combinations evaluated were the following (treatment designations within the abbreviations indicate the order of application): TW, TWS, WS, VW, VWS, TWLS, and VWLS. These combinations resulted in reductions ranging from 3.5 to 5.3 log CFU/cm2 in all three pathogen populations. The TW, TWS, WS, TWLS, and VWLS combinations were equally effective (P > 0.05), resulting in reductions ranging from 4.2 to 5.3 log CFU/cm2. When used individually, T, V, and S resulted in pathogen reductions ranging from 2.5 to 3.7 log CFU/cm2 Steam pasteurization consistently provided numerically greater pathogen reductions than T or V. Treatments T, V, and S were all more effective than W (which gave a reduction on the order of 1.0 log CFU/cm2) Steam pasteurization is an effective method for reducing pathogenic bacterial populations on surfaces of freshly slaughtered beef, with multiple decontamination procedures providing greatest overall reductions.
Keywords: Steam; Pasteurization; E. coli; Pathogens; Salmonella; Decontamination